2003
DOI: 10.1073/pnas.1532271100
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a photosystem II supercomplex isolated from Prochloron didemni retaining its chlorophyll a/b light-harvesting system

Abstract: Prochlorophytes are a class of cyanobacteria that do not use phycobiliproteins as light-harvesting systems, but contain chlorophyll (Chl) a͞b-binding Pcb proteins. Recently it was shown that Pcb proteins form an 18-subunit light-harvesting antenna ring around the photosystem I (PSI) trimeric reaction center complex of the prochlorophyte Prochlorococcus marinus SS120. Here we have investigated whether the symbiotic prochlorophyte Prochloron didemni also contains the same supermolecular complex. Using cells isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 38 publications
2
54
0
Order By: Relevance
“…Functional association of Pcb proteins with PSII-RC cores has also been shown in Prochlorococcus [17] and Prochloron [18] with similar structural arrangement around each individual RC core dimer. It has also been shown that Pcb proteins can bind to PSI to form an 18-mer antenna ring [16,17]; no such structure has as yet been identified in Acaryochloris.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Functional association of Pcb proteins with PSII-RC cores has also been shown in Prochlorococcus [17] and Prochloron [18] with similar structural arrangement around each individual RC core dimer. It has also been shown that Pcb proteins can bind to PSI to form an 18-mer antenna ring [16,17]; no such structure has as yet been identified in Acaryochloris.…”
Section: Discussionmentioning
confidence: 62%
“…Pcb proteins are normally found in cyanobacteria lacking phycobiliproteins, commonly called prochlorophytes, of which there are three well known examples; P. didemni [3], Prochlorothrix hollandica [14] and Prochlorococcus marinus [15]. In these organisms the Pcb proteins bind both Chl a and Chl b and function as outer light harvesting systems for PSI and PSII [16][17][18]. Since Acaryochloris contain phycobiliproteins that act as an outer light harvesting system for PSII [11,19,20], the question is raised as to the function of the Chl d-binding Pcb proteins in this unusual cyanobacterium, which we address in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Two major accessory light-harvesting and protection systems exist in cyanobacteria, PBPs (reviewed in ref. 37), and accessory chlorophyll-binding proteins (CBPs) (38)(39)(40). Like other ''alternative Chl'' cyanobacteria, A. marina does not construct the supramolecular PBP assemblies, the PBSs.…”
Section: Resultsmentioning
confidence: 99%
“…Prochlorococcus, which lack or have only very primitive PBPs, constitutively express their CBP systems (40). Conversely, the expression of the CBPIII (IsiA) is activated only under iron-stress conditions during which PBP expression is strictly repressed (43).…”
Section: Resultsmentioning
confidence: 99%
“…Research by Milligan and Harrison (2000) shows that the marine diatom T. pseudonana, known to produce flavodoxin, continued to release NO 2 2 under iron-limiting, light-saturating conditions, suggesting that the intracellular mechanisms leading to NO 2 2 release are more complicated. Perhaps not unexpectedly, Prochlorococcus has a unique light-harvesting antenna when grown under iron limitation that increases its competitive ability at the base of the euphotic zone (Bibby et al 2001(Bibby et al , 2003. The interactions between light, iron limitation, and phytoplankton release of NO 2 2 have not been directly studied, let alone quantified in conceptual models or in process-oriented field studies.…”
Section: Winter Mixingmentioning
confidence: 99%